2002
DOI: 10.1002/gcc.10027
|View full text |Cite
|
Sign up to set email alerts
|

Spectral karyotyping in patients with acute myeloid leukemia and a complex karyotype shows hidden aberrations, including recurrent overrepresentation of 21q, 11q, and 22q

Abstract: We used spectral karyotyping (SKY) to study 29 adults with acute myeloid leukemia and a complex karyotype containing one to nine abnormalities that were not fully identifiable by G-banding. SKY showed the origin of rings and unidentified material in unbalanced translocations in all cases and the origin of markers in most, allowing reinterpretation of 136 aberrations and discovery of three aberrations hidden in normal chromosomes. SKY confirmed 10 and refined the interpretation of three balanced aberrations rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 35 publications
4
78
0
Order By: Relevance
“…Recently, several studies using multicolor fluorescence in situ hybridization have shown that complex karyotypes with monosomies of chromosomes 5 and 7 often harbor marker chromosomes containing material from these chromosomes and that many deletions, including 5q deletions, have been shown to be unbalanced translocations. 57,58 Thus, the present conclusion concerning differences between whole and partial losses of chromosomes 5 and 7 may well be modified when more data based on molecular cytogenetics have been collected. The chromosomal abnormalities shown to be more common in de novo disease were +8 as a sole anomaly, balanced changes as such, t(8;21), t(9;22), t(15;17), inv (16), and 21q22 translocations in general in AML (Table 2) and −Y, 5q−, and 20q− as sole anomalies and +8 in MDS (Table 3).…”
Section: Discussionmentioning
confidence: 93%
“…Recently, several studies using multicolor fluorescence in situ hybridization have shown that complex karyotypes with monosomies of chromosomes 5 and 7 often harbor marker chromosomes containing material from these chromosomes and that many deletions, including 5q deletions, have been shown to be unbalanced translocations. 57,58 Thus, the present conclusion concerning differences between whole and partial losses of chromosomes 5 and 7 may well be modified when more data based on molecular cytogenetics have been collected. The chromosomal abnormalities shown to be more common in de novo disease were +8 as a sole anomaly, balanced changes as such, t(8;21), t(9;22), t(15;17), inv (16), and 21q22 translocations in general in AML (Table 2) and −Y, 5q−, and 20q− as sole anomalies and +8 in MDS (Table 3).…”
Section: Discussionmentioning
confidence: 93%
“…[10][11][12][13][14][15] Patient characteristics, karyotypes, results of FISH, and mutation status of TP53 and AML1 of the three cases are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon has been observed in approximately 2% of patients with childhood acute lymphoblastic leukemia (ALL), [6][7][8][9] but to our knowledge only in seven cases of de novo MDS and AML. [10][11][12][13][14][15] In these seven patients the mutational status of TP53 was not examined. In t-MDS and t-AML a similar amplification or duplication of chromosome band 11q23 including the unrearranged MLL gene has been observed in 17% of the patients closely associated with mutations of the TP53 gene.…”
Section: Introductionmentioning
confidence: 99%
“…Among the genetic markers that has been previously studied in CN-AML patients are Fms-related tyrosine kinase 3 gene (FLT3) mutations [2][3][4][5], the nucleophosmin gene (NPM1) mutations [6][7][8][9][10][11][12][13][14][15], ERG [16,17] and BAALC [18][19][20][21][22] expression levels. Although studies concerning the prognostic relevance of BAALC [18] and ERG expression [16,17] in adult AML patients with CN AML become fully clear; the studies regarding their expression and prognostic impact in pediatric AML are few and of controversial results.…”
Section: Introductionmentioning
confidence: 99%